Delirium, Subsyndromal Delirium, and Cognitive Changes in Individuals Undergoing Elective Coronary Artery Bypass Graft Surgery. Issue 4 (July 2015) - Li, Hsiu-Ching; Chen, Yih-Sharng; Chiu, Ming-Jang; Fu, Mei-Chiung; Huang, Guan-Hua; Chen, Cheryl Chia-Hui
Abstract : Background: The course of incident delirium and subsyndromal delirium (SSD) after cardiac surgery is not well studied. Objective: The aim of this study was to evaluate the course of incident delirium and SSD, their risk factors, and impact on patients' cognitive function after elective coronary artery bypass graft (CABG) surgery. Methods: Consecutive patients scheduled for an isolated CABG at a tertiary medical center in Taiwan were enrolled if they had no preoperative delirium symptoms. Delirium was assessed daily for 1 week after surgery using the Confusion Assessment Method. Subsyndromal delirium was defined as presenting with any core symptom below the diagnostic threshold for delirium. Cognitive function was assessed by the Mini-mental State Examination. Results: Of 38 participants, 7 had incident (first-time) delirium (18.4% incidence) and 13 had incident SSD (34.2% incidence). Whereas SSD usually lasted 1 day, delirium changed gradually to SSD to recovery and its symptomatology lasted longer. We identified 6 delirium risk factors: older age, more comorbidities, cardiac pulmonary bypass, blood transfusion, larger transfusion volume, and longer duration of intraoperative blood pressure less than 60 mm Hg. The frequencies of these risk factors for SSD were often intermediate between those of risk factors in groups with and without delirium. By hospital discharge, participants with delirium had the longest hospital stays and lowest cognitive scores, those with SSD had intermediate stays and scores, and those without delirium had the lowest stays and scores. Conclusion: Delirium and SSD after CABG are common. Greater number and severity of risk factors for delirium may predict increasingly poor outcomes, with the dose-response relationship between risk factors and outcomes for SSD intermediate between that for no symptoms and full delirium. Intervention trials are indicated, particularly for patients with a greater number and severity of predisposing and precipitating risk factors.